Relationship Knowledge Of Male Of Fertilizer Couple About Condom Contraception With Men's Participation Fertile Age In Using Condom Contraception In The New Neighborhood Of The Bamboo Field - Desi Anggraini; Rizky Andriani Bakara (Science Midwifery, 2020)
Family planning is an attempt to measure the number and distance of children desired. Family planning acceptors in Indonesia are 6,665,203 acceptors. Active family planning acceptors who use condoms are 182,626 acceptors (2.74%). Contraception is an attempt to prevent pregnancy. Condoms are sheaths or rubber made of various materials including rubber, plastic, and natural materials that are placed on the penis to collect sperm when a man reaches ejaculation during sexual intercourse. This study aims to determine the relationship between knowledge of men of childbearing age about condom contraception with the participation of men of reproductive age in using condoms. The research method used is cross sectional. The population in this study were all male couples of childbearing age in Neighborhood V of Baru Ladang Bambu sub-district, Medan Tuntungan District in 2020. The sample technique used was purposive sampling of 40 respondents through. The results of the analysis showed that the majority of male couples of childbearing age who had sufficient knowledge participated 52%, ages 20-29 60%, basic education (SD-SMP) 53%, the majority of male couples of childbearing age worked as farmers 97.5%, the majority of sources information from neighbors 42.5% of the results of the chi-square statistical test, namely p = 0.002. It is recommended to health workers in Neighborhood V, Baru Ladang Bambu sub-district to provide counseling about condom contraception and its health benefits.